2012
DOI: 10.3846/20294913.2011.649912
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Classification of Technology Foresight Methods / Nauja Technologijų Prognozavimo Metodų Klasifikacija

Abstract: Since the end of the twentieth century there is a noticeable worldwide paradigm shift in future studies which are so far based mainly on statistical methods. The development of a social, not only a strictly scientific vision of the future has become crucial. It appears that the biggest role in this context played technology foresight programs (whose origins go back even to the 70's), integrating traditional methods of forecasting as well as those derived from the social sciences, economics, management science,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 27 publications
0
35
0
4
Order By: Relevance
“…IC measure ment methods are commonly used in the context of corpo rate business management (Sveiby 1997;Sullivan 2000) and increasingly by universities (Leitner 2002;FH Joanneum IC Report 2010. Whereas, the method does not appear in the comprehensive list of foresight techniques presented by Popper (2008) and Magruk (2011). Additionally, the authors of the paper have found only one example of the use of IC methods by a strategic research institute in order to prepare its IC Report: the Austrian Institute of Technology (Leitner, Warden 2004), but this activity was not connected to fore sight.…”
Section: Foresight Methodsmentioning
confidence: 98%
“…IC measure ment methods are commonly used in the context of corpo rate business management (Sveiby 1997;Sullivan 2000) and increasingly by universities (Leitner 2002;FH Joanneum IC Report 2010. Whereas, the method does not appear in the comprehensive list of foresight techniques presented by Popper (2008) and Magruk (2011). Additionally, the authors of the paper have found only one example of the use of IC methods by a strategic research institute in order to prepare its IC Report: the Austrian Institute of Technology (Leitner, Warden 2004), but this activity was not connected to fore sight.…”
Section: Foresight Methodsmentioning
confidence: 98%
“…Magruk (2011). He identified 117 methods with the potential of use for foresight research and grouped them into 10 classes.…”
Section: The Current Classification Of Methods Used In Fta -A Literatmentioning
confidence: 99%
“…Analysis of the methods within the class (Georghiou et al 2008;Magruk 2011;Saritas et al 2014) source data analysis (Georghiou et al 2008;Magruk 2011;Saritas et al 2014) analysis of longterm (Cagnin et al 2008;Georghiou et al 2008;Magruk 2011;Saritas et al 2014) analysis of the action (Cagnin et al 2008) institutional analysis (Cagnin et al 2008;Georghiou et al 2008;Magruk 2011;Saritas et al 2014) stakeholder analysis (Cagnin et al 2008;Georghiou et al 2008;Magruk 2011;Saritas et al 2014) correspondence analysis (Georghiou et al 2008;Magruk 2011;Saritas et al 2014) life cycle costing (Gieraszewska,…”
Section: Step IVmentioning
confidence: 99%
“…He makes three basic suggestions about technology management which can be applied to foresight research. The first one indicates that qualitative and quantitative methods of technology management methodology should be integrated, which is analogous to research methodology of foresight that accommodates a combination of qualitative and quantitative methods as well as intermediate ones (Popper 2008;Magruk 2011a). The second suggestion is that the interdisciplinary char acter of technology management should be noted, so the research scope in technology management methods should be widened.…”
Section: Foresight and Technologymentioning
confidence: 99%